Development of Innovative Education in Pedagogy - Shukurova Ugiloy Umarovna (Peerian Journals Publishing, 2022)
In this scientific article, along with the creation of an innovative environment in the system of continuous education in our Republic, the innovative activities of educational institutions, the development of innovative education, trends and perspectives, and the implementation of innovative activities in the development of innovative education are discussed.
Keywords: innovation; innovative techniques; innovative education